Training for Social Development Staff at the World Bank, Volume 1. Main Report - Gross, Daniel R.; LeDuc, Matthew (World Bank, Washington, DC, 2013)
The social development family is facing a major challenge given the significant increase in lending made by the Bank in the last five years. Lending overall has more than doubled between FY05 and FY09; investment lending has increased by 82 percent and infrastructure lending by 125 percent. In this report, International Evaluation Group (IEG) suggests that the World Bank's safeguard policies are 'unbalanced' and narrowly conceived even in comparison to other Multilateral Development Banks (MDBs). The report challenges the Bank to consolidate and update its social policies. The purpose of this paper is to present a concept note on core training and accreditation program on social sustainability and social safeguards to Bank staff, including a comprehensive proposal of the training and program, main objectives, content and scope of the course (social sustainability, social analysis social assessment, demand for good governance, youth, gender, 'fragility, conflict, crime and violence', social impacts of climate change, community driven development, social safeguard policies-involuntary resettlement, indigenous peoples, cultural property) target audiences, duration and methodologies according to the audiences, and estimated budget.